Preoperative misdiagnosis of pancreatic and periampullary cancer in patients undergoing pancreatoduodenectomy: A multicentre retrospective cohort study. Issue 10 (October 2021) - van Roessel, Stijn; Soer, Eline C.; Daamen, Lois A.; van Dalen, Demi; Fariña Sarasqueta, Arantza; Stommel, Martijn W.J.; Molenaar, I. Quintus; van Santvoort, Hjalmar C.; van de Vlasakker, Vincent C.J.; de Hingh, Ignace H.J.T.; Groen, Jesse V.; Mieog, J. Sven D.; et al.
Abstract: Introduction: Whereas neoadjuvant chemo(radio)therapy is increasingly used in pancreatic cancer, it is currently not recommended for other periampullary (non-pancreatic) cancers. This has important implications for the relevance of the preoperative diagnosis for pancreatoduodenectomy. This retrospective multicentre cohort study aimed to determine the frequency of clinically relevant misdiagnoses in patients undergoing pancreatoduodenectomy for pancreatic or other periampullary cancer. Methods: Data from all consecutive patients who underwent a pancreatoduodenectomy between 2014 and 2018 were obtained from the prospective Dutch Pancreatic Cancer Audit. The preoperative diagnosis as concluded by the multidisciplinary team (MDT) meeting was compared with the final postoperative diagnosis at pathology to determine the rate of clinically relevant misdiagnosis (defined as missed pancreatic cancer or incorrect diagnosis of pancreatic cancer). Results: In total, 1244 patients underwent pancreatoduodenectomy of whom 203 (16%) had a clinically relevant misdiagnosis preoperatively. Of all patients with a final diagnosis of pancreatic cancer, 13% (87/679) were preoperatively misdiagnosed as distal cholangiocarcinoma (n = 41, 6.0%), ampullary cancer (n = 27, 4.0%) duodenal cancer (n = 16, 2.4%), or other (n = 3, 0.4%). Of all patients with a final diagnosis of periampullary (non-pancreatic) cancer, 21% (116/565) were preoperatively incorrectly diagnosed as pancreatic cancer. Accuracy of preoperative diagnosis was 84% for pancreatic cancer, 71% for distal cholangiocarcinoma, 73% for ampullary cancer and 73% for duodenal cancer. A prediction model for the preoperative likelihood of pancreatic cancer (versus other periampullary cancer) prior to pancreatoduodenectomy demonstrated an AUC of 0.88. Discussion: This retrospective multicentre cohort study showed that 16% of patients have a clinically relevant misdiagnosis that could result in either missing the opportunity of neoadjuvant chemotherapy in patients with pancreatic cancer or inappropriate administration of neoadjuvant chemotherapy in patients with non-pancreatic periampullary cancer. A preoperative prediction model is available on www.pancreascalculator.com .